2010
DOI: 10.4238/vol9-4gmr912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thai black sticky rice extract on oxidative stress and lipid metabolism gene expression in HepG2 cells

Abstract: ABSTRACT. Anthocyanins, which are found in some food, including Thai black sticky rice, are reported to have health-promoting properties. Oxidative stress plays a major role in the pathogenesis of many degenerative diseases induced by free radicals, such as cardiovascular disease, stroke and cancer. We evaluated the anthocyanin-rich extract (ARE) from Thai black sticky rice for antioxidative and antihyperlipidemic effects on HepG2 cells. Cell viability was investigated with the neutral red assay and the MTT as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The 200 and 400 mg/L TLE doses progressively increased CYP3A4 and PPARg gene expression, respectively. This particular biological activity of TLE was similar to that of black sticky rice extract, which acted in a concentration-dependent fashion with a biphasic "up then down" effect on LDLR mRNA expression in HepG2 cells (Sangkitikomol et al, 2010). PPARg plays essential roles in metabolic syndromes.…”
Section: Discussionmentioning
confidence: 67%
“…The 200 and 400 mg/L TLE doses progressively increased CYP3A4 and PPARg gene expression, respectively. This particular biological activity of TLE was similar to that of black sticky rice extract, which acted in a concentration-dependent fashion with a biphasic "up then down" effect on LDLR mRNA expression in HepG2 cells (Sangkitikomol et al, 2010). PPARg plays essential roles in metabolic syndromes.…”
Section: Discussionmentioning
confidence: 67%
“…Other natural products have been used to examine lipid lowering effects, such as hesperidin, naringin (Jung et al, 2006), resveratrol (Do et al, 2008), and curcumin (Jang et al, 2008), which could also decrease hepatic HMG-CoAR. In contrast, red wine polyphenols (Pal et al, 2003) and anthocyanins in black sticky rice (Sangkitikomol et al, 2010) have been shown to increase hepatic LDLR. In addition, β-sitosterol in M. oleifera leaves has also been shown to decrease intestinal uptake of cholesterol (Lin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…47 Also, oxidative stress-induced ROS production was observed in HepG2 cells treated with an anthocyaninrich extract from Thai black sticky rice. 48 According to literature data the in vitro antioxidant potential of anthocyanins is related to their highly electrondeficient form of flavylium cation. 44 Crucial for cell-target interaction seems to be the ortho-3 0 ,4 0 -dihydroxy groups on the B ring.…”
Section: Intracellular Rosmentioning
confidence: 99%